Industrial training report: Netherlands Maritime University College (NMUC) - Zainal, Nuratiqah Nalieta (Faculty of Business and Management, 2023)
This report is discussing about my industrial training programme at Netherlands Maritime University College (NMUC). I have concluded my six-month industrial training from 1st March 2023 until 15th August 2023. Therefore, I discuss about every significant aspect of the organization that I observed during my industrial training programme, including the product that offered by Netherlands Maritime University College (NMUC). My six-month industrial training at Netherlands Maritime University College (NMUC) began with a memorable experience as I gained a lot of new experience from this organization. This university was founded in 2011 as a maritime education, training, research, and consulting institution. NMUC has assisted more than 4,000 students at both the City Campus in Johor Bahru and the EduCity Campus in Iskandar Puteri. Moreover, this company also offered maritime programme in diploma, bachelor as well as foundation which are Diploma in Maritime Transportation Management, Diploma in Port Management, Diploma in Shipping Management, Diploma in Maritime Occupational Safety and Health, Diploma in Maritime Law, Bachelor in Maritime and Logistic, Bachelor in Maritime Occupational Safety and Health and Foundation in Business. Moreover, during my six-month industrial training programme I has been assigned a few tasks from the staff in the organization. I've been assigned to the department of sales and marketing, where I am responsible for assisting with administrative and marketing tasks. This is because my supervisor, Mr. Ibrahim bin Hamzah told me that he wants me to depart from this company with a wealth of knowledge and an understanding of how to perform work from all angles. As for example, I learned how to handling phone calls, prepare full documents for event, how to be good consultant, prepare an offer letter, settle up the refund with finance department, be one of the members in the registration days in campus, responsible for open booth at school as well as responsible for career day in school. Furthermore, in this report I already carried out the SWOT analysis that I discovered in the Sales and Marketing Department. Initially, it was challenging for me to identify the department's weaknesses and strengths, but the longer I stayed, the more I became aware of the department's advantages and disadvantages for both external and internal. Therefore, I have also enumerated a portion of the explanation and recommendation regarding the SWOT analysis. To sum it up, the experience as well the knowledge that I gained in this organization can help me in the real work situation.